Naming Strategies in Urarina (Isolate, Peru) Ethnozoological Nomenclature - Peña Torrejón, Jaime (2022)
This paper is a first detailed study of the ethnozoological nomenclature in Urarina, an Amazonian isolate language spoken in Loreto, Peru. Based on a corpus of more than 250 lexical items gathered through fieldwork, we describe and analyze the main linguistic strategies used in the formation of Urarina animal names. As a result, eight naming strategies are proposed for Urarina animal nomenclature, and the relationship between these strategies and the formation of simple and complex lexemes is discussed. The paper contributes not only to the documentation and description of an Amazonian isolate, but also to the comparison, both typological and areal, with other languages of the region.